Phryn. Com. fr. 34 K.-A.: un esempio di ‘ghost-word’ - Stama, Felice (Rivista di Filologia e di Istruzione Classica, 2014)
Abstract In the most important modern Greek dictionaries we find an entry for the word περίπολις, which is recorded as a coinage of the comic poet Phrynichus in fr. 34 K.-A. from his lost play entitled Muses (405 B.C.); but, if we consider the textual tradition of the fragment (preserved by Pollux 7, 203), this word turns out to be a conjecture by the Dutch scholar Tiberius Hemsterhuys in 1706.